From non-human animals’ laboratory to where? Retrospective analysis of pedagogical practices in EAB (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The development of pedagogical resources for teaching Behavior Analysis follows the scenario in which alternatives to the use of non-human animals in the laboratory are sought. The aim of this study was to investigate the characteristics of the didactic strategies used by professors of Brazilian instituitions in the practical discipline of EBA over the ten years following the enactment of Law 11.794/2008. A convenience sample of 40 professors from public higher education institutions who responded to semi-structured interviews was recruited. Although the results demonstrate the supremacy of the use of animals in the teaching laboratory, there was heterogeneity in the pedagogical activities conducted with human beings and the use of computer simulators, in addition to institutions that ended the practices. The variables that affect the lack of consensus on the maintenance or not of the laboratory with non-human animals and the need to invest in pedagogically efficient resources to substitute the operating laboratory are discussed.
Keywords: teaching; teaching resources; experimental behavior analysis; teaching laboratory; non-human animals